2022
DOI: 10.1002/em.22477
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA polymorphisms and colorectal cancer risk: Progression and future perspectives

Abstract: Colorectal cancer (CRC) is one of the most common cancers causing death worldwide. Many long noncoding RNAs (lncRNAs) have possible carcinogenic or tumor suppressor functions. Some lncRNA polymorphisms are useful for predicting cancer risk, and may help advance personalized therapy management. While the use of lncRNAs as biomarkers is promising, there are still drawbacks, and further studies are needed to verify the consistency of current outcomes in large-scale populations and different ethnicities. Single nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…At first, it was thought to have no biological function, but the results of many experiments tell us that lncRNAs regulate gene expression at many levels in the form of RNA, such as transcription, posttranscriptional level, and epigenetics [ 29 , 30 ]. lncRNAs work mainly through the following four ways: first, induction, lncRNAs can bind to a specific miRNA, which can indirectly regulate the target gene; second, lncRNAs can act as a signal molecule on the pathway and regulate the upstream- and downstream-related genes of its target gene [ 31 , 32 ]. Third, by guiding the relevant RNA-binding proteins, lncRNAs are able to mediate the target genes via cis- or trans-regulation to specific protein complex sites [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…At first, it was thought to have no biological function, but the results of many experiments tell us that lncRNAs regulate gene expression at many levels in the form of RNA, such as transcription, posttranscriptional level, and epigenetics [ 29 , 30 ]. lncRNAs work mainly through the following four ways: first, induction, lncRNAs can bind to a specific miRNA, which can indirectly regulate the target gene; second, lncRNAs can act as a signal molecule on the pathway and regulate the upstream- and downstream-related genes of its target gene [ 31 , 32 ]. Third, by guiding the relevant RNA-binding proteins, lncRNAs are able to mediate the target genes via cis- or trans-regulation to specific protein complex sites [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies found that some lncRNAs contain short open reading frames (sORFs), which can encode small proteins or micropeptides to exert their physiological roles [ 11 , 12 ]. Aberrant lncRNA expression, which could be caused by single nucleotide polymorphism (SNPs), copy number alterations, and mutations, has been found in various tumors such as colorectal cancer (CRC), thyroid cancer, and ovarian cancer (OC), and is closely related with cancer hallmarks and malignant transformation [ 13 , 14 , 15 ]. Thus, lncRNAs have gained attention as novel biomarkers for tumors and as targets for antitumor therapeutic strategies [ 16 ].…”
Section: Introductionmentioning
confidence: 99%